Anticarcinogenic cationic peptides derived from tryptic hydrolysis of β-lactoglobulin - Ibrahem, Eman; Osman, Ali; Taha, Hefnawy; Abo El-Maati, Mohamed F.; Sitohy, Basel; Sitohy, Mahmoud (Frontiers in Molecular Biosciences, 2025)
IntroductionThis study investigated the tryptic hydrolysis of β-lactoglobulin (BLG) for 30, 60, 90, and 120 min at 1/200 E/S (enzyme/substrate ratio, w/w) to prepare potentially anticarcinogenic peptides.MethodsThe properties of hydrolysates were characterized, including degree of hydrolysis, free amino acids, SDS-PAGE, FTIR, and antioxidant activity employing DPPH-assay, β-carotene/linoleic acid, and FRAP assay.ResultsBLG tryptic hydrolysate produced after 60 min hydrolysis recorded the highest antioxidant activity, and LCMS analysis revealed 162 peptides of molecular masses ranging from 800 to 5671Da, most of them are of hydrophobic nature. Within the low-MW peptide group (24 peptides), there were nine hydrophobic basic (HB) and seven hydrophobic acidic (HA), representing 38% and 29%, respectively. The HB peptides may be responsible for the considerable biological activity of the hydrolysate. With dominant basic character supporting the carcinogenic activity of this hydrolysate. The in vitro anticancer activity against Mcf-7, Caco-2, and A-549 human cancer cell lines proliferation by MTT assay recorded IC50% at 42.8, 76.92, and 45.93 μg/mL, respectively. Treating each cell line with IC50% of the hydrolysate for 24 h increased the apoptosis by enhancing the expression of caspase-9 by 5.66, 7.97, and 3.28 folds over the untreated control and inhibited angiogenesis by reducing VEGFR-2 expression by about 56, 76, and 70%, respectively, indicating strong anticancer and antiangiogenic actions on human cancer cells. BLG tryptic hydrolysate may serve as a natural anticarcinogenic agent. The results of this study demonstrated that BLG hydrolysates have direct anticancer and antiangiogenic effects on human cancer cells. The chemical composition and characteristics of the BLG tryptic hydrolysate influence these biological and anticancer activities. The tryptic hydrolysates were generally effective against the three cancer cell lines studied (Mcf-7, Caco-2, and A-549). This effectiveness was assessed by measuring cell proliferation using the MTT assay and by evaluating their impact on angiogenesis through inhibition of VEGFR-2 activity.DiscussionFuture studies may focus on enhancing the anticarcinogenic effectiveness of the peptides by isolating and evaluating the most prominent individual peptide and varying the treatment conditions.